Bioinks: 3D Printing of Mechanically Stable Calcium‐Free Alginate‐Based Scaffolds with Tunable Surface Charge to Enable Cell Adhesion and Facile Biofunctionalization (Adv. Funct. Mater. 9/2019). (27th February 2019) - Lin, Zifeng; Wu, Mingming; He, Huimin; Liang, Qingfei; Hu, Chengshen; Zeng, Zhiwen; Cheng, Delin; Wang, Guocheng; Chen, Dafu; Pan, Haobo; Ruan, Changshun
Abstract : In article number1808439, Dafu Chen, Haobo Pan, Changshun Ruan, and co‐workers describe a mechanically stable alginate/ϵ‐polylysine scaffold with a tunable surface charge fabricated by 3D printing in physiological conditions for tissue regeneration. The tunable surface charge of the scaffolds is varied until the optimal design is defined for improving cell adhesion and biofunctionalization, with the ultimate goal of enhancing Alg‐based scaffold bioactivity.